The Most Important Maglev Applications - Hamid Yaghoubi (Journal of Engineering)
The name maglev is derived from magnetic levitation. Magnetic levitation is a highly advanced technology. It has various uses. The common point in all applications is the lack of contact and thus no wear and friction. This increases efficiency, reduces maintenance costs, and increases the useful life of the system. The magnetic levitation technology can be used as an efficient technology in the various industries. There are already many countries that are attracted to maglev systems. Many systems have been proposed in different parts of the worlds. This paper tries to study the most important uses of magnetic levitation technology. The results clearly reflect that the maglev can be conveniently considered as a solution for the future engineering needs of the world.